Rancangan Sistem Pemantauan Struktur Terintegrasi Berbasis Sensor Pada Tahap Konstruksi Gedung Bertingkat - Arnold Santoso; Yongki Alexander Tanne (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
The construction of high-rise buildings involves a high level of structural risk, particularly during the construction phase when structural elements have not yet reached their design capacity and are still subjected to significant temporary loads. Current supervision practices that rely primarily on visual inspections and conventional methods are considered insufficient for detecting changes in structural behavior in an early and objective manner. This study aims to design an integrated structural monitoring system capable of connecting various types of sensors and generating real-time data to support continuous monitoring and an early warning mechanism. The research method employed is a systematic literature review of recent studies related to structural health monitoring, sensor technologies, and Internet of Things (IoT)-based systems. Based on the review results, an integrated monitoring system architecture, system workflow, and sensor placement strategy for major structural elements and critical areas of the building are developed. The results indicate that the proposed IoT-based system is able to comprehensively represent structural behavior, support early detection of potential risks or initial indications of structural failure, and serve as an initial reference for the development of more reliable and applicable structural monitoring systems. Keywords: structural monitoring, integrated sensors, IoT, high-rise buildings, construction